Sex for Law, Sex for Psychiatry: Pre-Sex Reassignment Surgical Psychotherapy in Turkey - Zengin, Aslı (Anthropologica, 2014)
In Turkey, production of "transsexuality" as a medico legal category dates back to 1988. Amendments in 2002 to the regulation of sexual transition shaped their present form, which requires psychiatric observation during the transition period, putting trans people under strict institutional supervision and evaluating them in terms of their gender role performance. Focusing on trans peoples’ experiences of psychiatric observa tion, this paper illustrates the medical steps trans people take to collect evidence of their "true" sex, and shows how psychia trists evaluate these steps. It explores how negotiations between doctors and trans people work upon conflicting meanings of bodily time, sex, gender and sexuality.